O40-3 Effects of working conditions on airway inflammation in compost workers. (1st September 2016) - Demange, Valerie; Duquenne, Philippe; Reboux, Gabriel; Grzebyk, Michel
Abstract : Rationale and objectives: Compost workers have more airway irritation symptoms and increased inflammation markers than non-exposed workers. We studied which activities and processed wastes are involved. Methods: 90 compost workers were followed-up for 18 months with a medical examination every 6 months. At each visit, two questionnaires on the preceding six-months, regarding the tasks of a typical work-week and respiratory health and irritation symptoms, were administered. Fractional exhaled nitric oxide (NOe) measures, spirometry and a methacholine challenge test (MCT) were performed. Skin prick-tests for common aeroallergens were performed on the first visit, and immunoglobulin (Ig) E and G specific to airborne microorganisms commonly observed in composting plants were quantified on two visits. Results: Sixty-one subjects (68%) worked in 20 green waste (GW) plants and 29 (32%) in 15 sewage sludge (SS) plants. Thirteen workers (14%) were drivers or mechanics considered as having low exposure. Thirty-seven workers were atopic (42%) and 12 (13%) had ever-asthma. Workers in plants processing the highest quantities of waste had more upper (OR = 7.5, IC95%=[1.3;42.7]) and lower (OR = 1.05, IC95%=[1.0;1.1]) airway irritation symptoms and digestive symptoms (OR = 1.23, IC95%=[1.0;1.5]), and more frequently altered FVC (OR = 1.3, IC95%=[1, 1;1, 5]) and FEV1 (OR = 1.2, IC95%=[1.0;1.4]). Mixing materials (OR = 1.04, IC95%=[1.0;1.1]) and handling compost (OR = 1.13, IC95%=[1.0;1;2]) were tasks associated with more asthma-like symptoms. Cleaning activities were associated with a higher MCT dose-response slope (β = −0.010, IC95%=[−0.019;−0.001]). Workers in GW plants had a higher risk of having an increased NOe than workers in SS plants (OR = 45.8, IC95%=[2.6;808.2]). Less exposed workers had a lower level of IgE specific to actinomycetes (exp(β)=1.17, IC95%=[1.04;1.32]). Conclusion: This is the first time the characteristics of the plants, tasks performed and types of waste processed have been linked to markers of airway inflammation and symptoms in compost workers.